An innovative intermittent-vacuum assisted thermophilic anaerobic digestion process for effective animal manure utilization and treatment. (November 2017) - Zhang, Renchuan; Anderson, Erik; Addy, Min; Deng, Xiangyuan; Kabir, Fayal; Lu, Qian; Ma, Yiwei; Cheng, Yanling; Liu, Yuhuan; Chen, Paul; Ruan, Roger
Highlights: Thermophilic AD inhibitions of FAN and H2 S were removed and recovered by coupling the IVS. An innovative multi-unit operation system/process for LSM complete utilization was developed. 98% of ammonia (TAN) and 38% organic nitrogen (ONt) were recycled by the IVS-TAD. 50% methane yield increase and 40% hydrolysis time reduction were achieved by IVS-TAD. Abstract: Intermittent-vacuum stripping (IVS) was developed as a pretreatment for thermophilic anaerobic digestion (TAD) to improve methanogenesis and hydrolysis activity through preventing free ammonia and hydrogen sulfide (H2 S) inhibition from liquid swine manure (LSM). Over 98% of ammonia and 38% organic nitrogen were removed in 60 min from 55 °C to 85 °C with vacuum pressure (from 100.63 ± 3.79 mmHg to 360.91 ± 7.39 mmHg) at initial pH 10.0 by IVS. Thermophilic methanogenesis and hydrolysis activity of pretreated LSM increased 52.25% (from 11.56 ± 1.75% to 17.60 ± 0.49%) in 25 days and 40% (from 10 days to 6 days) in bio-methane potential assay. Over 80% H2 S and total nitrogen were removed by IVS assistance, while around 70% nitrogen was recycled as ammonium sulfate. Therefore, IVS-TAD combination could be an effective strategy to improve TAD efficiency, whose elution is more easily utilized in algae cultivation and/or hydroponic system.